On the Oxidation Kinetics of Alumina- and Chromia-Forming Alloys: Growth of Scale with the Change of Reaction Area - Irakli Nakhutsrishvili; Revaz Kokhreidze; Giorgi Kakhniashvili; Irakli Javakhishvili (Progress in Chemical Science Research Vol. 9, 2023)
On the basis of Evans’ conceptual theory, a new equation of the growth of scale with the change of the reaction area has been tested and formulas obtained that allow constructing the kinetic curves of oxidation both for specific heat-resistant alloys (FeCr, FeCrAl) and for possible, hypothetical objects of research. The study of the oxidation processes of alloys FeCr(La) and FeCrAl(La) in air at \(1200-1400^°\) shows the deviation of the oxidation kinetics from parabolic. This is due to the presence of diffusion barriers from lanthanum chromite LaCrO3 in the scale. The processes of high-temperature oxidation of FeCr(Y) and FeCr(Ce) alloys are also considered.